2008
DOI: 10.3928/15428877-20080701-09
|View full text |Cite
|
Sign up to set email alerts
|

Regression of Vasoproliferative Tumor with Systemic Infliximab

Abstract: The anti-tumor necrosis factor (TNF) monoclonal antibody infliximab inhibits the pleiotropic actions of TNF and is widely used for the treatment of inflammatory diseases, such as uveitis. A pathogenetic role of TNF in ocular inflammatory conditions has recently emerged. The authors describe a patient with collagen mixed disease who had decreased vision in the left eye. Fundus examination disclosed bilateral peripheral vasoproliferative tumors and macular edema in the left eye. The patient underwent treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 4 publications
0
6
0
1
Order By: Relevance
“…The details of treatment methods for RVPTs have been published and is beyond the scope of this study. 9,11,[13][14][15]18,24,26,27,29,36,40 In conclusion, a number of pediatric-related ocular conditions appear to predispose patients to the development of secondary RVPT. Ophthalmologists, particularly pediatric ophthalmologists and retinal specialists, should be aware of secondary RVPTs and their various ocular and nonocular associations.…”
Section: Discussionmentioning
confidence: 96%
“…The details of treatment methods for RVPTs have been published and is beyond the scope of this study. 9,11,[13][14][15]18,24,26,27,29,36,40 In conclusion, a number of pediatric-related ocular conditions appear to predispose patients to the development of secondary RVPT. Ophthalmologists, particularly pediatric ophthalmologists and retinal specialists, should be aware of secondary RVPTs and their various ocular and nonocular associations.…”
Section: Discussionmentioning
confidence: 96%
“…Japiassú et al reported an isolated case of bilateral RVPTs that showed regression after systemic treatment with infliximab (antibo dy anti tumor necrosis factor) for associated mixed collagen disea se (30) . In spite of being an isolated report, it is worth of note when we consider the known association of RVPTs with inflammatory ocular processes.…”
Section: Immunomodulatorsmentioning
confidence: 99%
“…TNFα is considered a therapeutic target for several inflammatory diseases. [26][27][28][29][30][31] Anti-TNFα biologics such as Adalimumab (ADA) or Infliximab are used to treat inflammatory disorders because of their effectiveness in blocking TNFα binding to its receptors TNFR1 and TNFR2. It is believed that this blockade reduces inflammation and cell death (in the form of apoptosis or other apoptosis-independent mechanisms).…”
Section: Introductionmentioning
confidence: 99%